Spinal Epidural Lipomatosis: A Review of Pathogenesis, Characteristics, Clinical Presentation, and Management. Issue 6 (September 2019) - Kim, Keonhee; Mendelis, Joseph; Cho, Woojin
Study Design: Narrative review of available literature. Objective: To summarize current trends in pathogenesis and management of spinal epidural lipomatosis (SEL) and suggest areas where more research would be of benefit. Methods: The available literature relevant to SEL was reviewed. PubMed, Medline, OVID, EMBASE, Cochrane, and Google Scholar were used to review the literature. Institutional review board approval is not applicable for this study. Results: This article clearly summarizes current trends in the pathogenesis and management of SEL. Conclusions: Possible etiologies of SEL include exogenous steroid use, endogenous steroid hormonal disease, obesity, surgery induced, and idiopathic disease. Comorbidities such as acquired immunodeficiency syndrome and Scheuermann's disease have also been implicated in the pathogenesis of SEL. Steroid-induced SEL seems to have a proclivity for the thoracic region of the spine and has a higher incidence of paraplegia when compared with other forms. Several treatment modalities exist for SEL and are dictated by the underlying cause of the disorder. These include weight reduction, cessation of steroid medications, treatment of underlying endocrine abnormalities, and surgical decompression. Conservative treatments generally aim to decrease the thickness of adipose tissue in the epidural space, but the majority of patients tend to undergo surgical decompression to relieve neurologic symptoms. Surgical decompression provides a statistically significant reduction in symptoms, but postoperative mortality is high, influenced primarily by the patient's preoperative comorbidities. Physicians should consider the underlying cause of SEL in a given patient before pursuing specific treatment modalities, but alarm symptoms, such as the development of acute cauda equina syndrome, should likely be treated with urgent surgical decompression.